Electrochemical detection and characterization of caffeine in selected tea samples using polyglycine modified Carbon paste electrode - Dereje Yenealem; Fetene Michu; Santhi Raju Pilli; Dessie Tibebe (South African Journal of Chemical Engineering)
Glycine was electro-polymerized against a carbon paste electrode (CPE) to produce a polymer film via the electro-oxidation process comprising amino (-NH2) and carboxylic (-COOH) groups, by a cyclic voltammetric. The electrochemical oxidation of caffeine was examined in 0.2 M phosphate buffer solution (PBS). The Polyglycine modified Carbon Paste Electrode (PGMCPE) demonstrates greater electrocatalytic activity for caffeine as compared to the unmodified CPE (UNMCPE). This made it suitable for analyzing caffeine owing to its increased electrode surface area and/or improved electron transport at the electrode surface. By varying the concentration range from 0.05 to 0.9 mM, the relationship between peak current and caffeine concentration was studied and this produced a correlation coefficient of R2 = 0.9987. This method was extremely capable of evaluating caffeine concentrations. Square wave voltammetry (SWV) was utilized to assess the caffeine in tea samples. The sample was analyzed with square wave voltammetry and was made easier with an ideal pH of 12.0. Additionally, the caffeine levels in a tea sample were successfully measured using the linear range and detection limit, and the results showed a good limit of detection (LOD) in comparison to previous literature.